Feeding inhibitory effect of some plant extracts on jute hairy caterpillar (Spilosoma obliqua) - CHOWDHURY, H; KAR, C S; SARKAR, S K; TRIPATHI, M K (The Indian Journal of Agricultural Sciences, 2012)
Azadirachtin (50% pure), along with turmeric oil isolated from rhizome powder of Curcuma longa and leaf extracts of tulsi (Ocimum sanctum), eucalyptus (Eucalyptus globulas) and sisal (Agave sisalana) were tested for feeding inhibition effect on third instar larvae of jute hairy caterpillar, S. obliqua. About 44.84% to 69.78% feeding inhibition was exhibited by azadirachtin at 0.1% to 0.5% conc. At 0.5% and 0.4% conc., 67.25% and 52.29% feeding inhibition was exhibited by turmeric oil. Eucalyptus, tulsi, and sisal extracts were less active than azadirachtin and tumeric oil. At 0.5% conc., azadirachtin and turmeric oil exhibited around 40% larval mortality, whereas 30% to 48.14% larval mortality was recorded at 0.2% to 0.5% conc. of tulsi extract.